Discourse ethics, power, and legitimacy: The ideal of democracy and the task of critical theory in Habermas. - Payrow Shabani, Abdollah. (University of Ottawa (Canada), 2000)
My thesis is concerned with the efficacy of Habermas' critical theory as an articulation of emancipatory interest, by way of critical diagnosis of social reality, which will make the ideal of free society possible. In his earlier theory of communicative action, he introduced a distinction between "the lifeworld" (the sphere of communicative interaction geared toward understanding) and "systems" (the spheres of strategic action steered by media of power and money). On this model, the pathologies of modern society were understood in terms of the colonization of the lifeworld by the systems, and emancipation was understood as preventing this colonization. In his recent works, however, this older model is seen as unable to account for legitimate power: i.e., it is unable to explain how citizens can convert their communicative understanding developed in the lifeworld into government policies. This leads Habermas to redefine the possibility of free society, emancipation, in terms of legitimate lawmaking. The turn to legal theory in Between Facts and Norms is anchored in the concept of modern law, which is situated between the lifeworld and system and as such is said to mediate between the two. Legitimate lawmaking is understood as the result of institutionalized procedures of public deliberation, which convert citizens' practices of self-determination, in the form of communicative and participatory rights, into the binding decision of political power. I will argue that the constructed concept of law, as what brings the insight of moral norms to bear upon the context of practical life, sits uncomfortably between the lifeworld and system. By aligning so closely the concepts of legitimate law, communicative power, and political system, Habermas' new approach fails to ensure emancipation since it legitimizes the political power as exercised in liberal-democratic states. I contend that the critical thrust of Habermas' theory can be regained by borrowing from the insights of postmodern political theory. Specifically, I will draw upon Foucault's analysis of power, which goes beyond the limitations of the consensus/coercion model of Habermas' view, and Derrida's deconstruction of law, which recovers the critical distance between the utopian ideal of justice and the real-existing political system.
Keywords: Philosophy.